Detection of Alternative Drugs for Illegal Injection Based on Surface-Enhanced Raman Spectroscopy - Bao, Lin; Han, Siqingaowa; Sha, Xuanyu; Zhao, Hang; Liu, Yuping; Lin, Dianyang; Hasi, Wuliji (Journal of Spectroscopy, 2019)
Promethazine and scopolamine are two major components of a drug commonly used as a substitute for heroin addiction but with its own potential for abuse. Here, surface-enhanced Raman spectroscopy experiments were combined with density functional theory computations of the Raman frequencies of promethazine. The enhancement of the SERS substrate was optimized by contrast detection of silver nanoparticles. The optimized substrate was used to detect scopolamine, promethazine and their mixtures. Several mixtures of different concentrations were detected and analyzed. The approach of rapid identification and monitoring of drugs will become an important tool in the detection and control of illicit drug use.